An aggregation-induced conformation locking strategy facilitates the activation of lipase biocatalyst - Anlian Huang; Zhi-Wei Li; Lihong Guo; Ningyi Zhong; Linjing Tong; Yanbin Xu; Xiaomin Ma; Fang Zhu; Guosheng Chen; Siming Huang; Gangfeng Ouyang (Nature Communications)
Abstract Lipase represents one of the most important industrial biocatalysts, with a global market value of $590.5 million by 2020. However, their catalytic efficiency is often hindered by a closed “lid” conformation. Here, we present an aggregation-induced conformation locking strategy that enables the facile synthesis of highly activated lipase hybrid biocatalysts. Lipase is self-activated into an open-lid conformation via solvent-mediated aggregation, followed by conformational locking within a two-dimensional metal-organic framework (MOF). The resulting MOF biocatalyst provides high accessibility to the locked lipase aggregates through its long-range ordered pore channels, achieving a hydrolytic efficiency 5.30 times greater than that of native lipase. To the best of our knowledge, this represents a record-high activation efficiency for ester hydrolysis among the reported lipase-based hybrid biocatalysts to date. We also demonstrate its feasibility to catalytically accelerate transesterification and esterification reactions, showing up to as 6.64 times higher yield than native lipase and impressive recyclability.